Azithromycin-carrying and microtubule-orientated biomimetic poly (lactic-co-glycolic acid) scaffolds for eyelid reconstruction - Xu, Peifang; Chen, Pengjie; Gao, Qi; Sun, Yiming; Cao, Jing; Wu, Han; Ye, Juan (Frontiers in Medicine, 2023)
Tarsal plate repair is the major challenge of eyelid reconstruction for the oculoplastic surgeon. Synthetic tarsal plate substitute can be an effective way to alleviate homologous grafts shortage, immune rejection of xenogenic substitutes and infection risks. An ideal substitute should imitate the microstructure and mechanical strength of natural eyelid. In this study, we examined the feasibility of fabricating microtubule-orientated poly(lactic-co-glycolic acid) (O-PLGA) scaffolds with interconnected pores by an improved thermal-induced phase separation technique. We successfully constructed O-PLGA using 1,4-dioxane as the first solvent and benzene or water with lower freezing point as the second solvent. Azithromycin was loading into the O-PLGA scaffolds, intending to reduce infection risks and enhance resolution of postoperative inflammation. The O-PLGA could guide two eyelid target cells, fibroblast and primary rat meibomian gland epithelial cells(rMGCs), to better grow along the microtubule direction of the scaffolds. Three PLGA scaffold were implanted into rabbit eyelid defect in vivo for 8 weeks to evaluate their inductive tissue repair function. Histological analysis showed a better repair effect of the O-PLGA scaffolds, with a matched rate between O-PLGA degradation and eyelid tissue integration. The O-PLGA scaffolds is a promising alternative for eyelid tarsal plate substitutes.